Gender appraisal of technological and psychological dynamics of farmers' club - PONNUSAMY, KUPPUSAMY; MOHAMMAD, ASIF (The Indian Journal of Agricultural Sciences, 2015)
Farmers' clubs are being promoted by NABARD since 1982 with a mission to develop rural areas through credit, farm technology and capacity building. A study was conducted to assess the women's participation vis a vis men in the farmers club in various farm activities and consequent impact on socio-economic and technological empowerment of both the genders. Nayagarh and Cuttack districts of Odisha were identified through random sampling. The sample for the study consisted of 52 members from farmers' club from each district with 12 females in Cuttack and 14 females in Nayagarh. Maximum respondents belonged to middle age (36-50 years) and had school education. Women were motivated to become members in order to avail the benefits of government schemes. But they remained as passive listeners in club meeting. Due to dominant behaviour of some male members, women preferred to involve in women headed/dominant farmers clubs. The present findings reveal a direction to make the agriculture inclusive and sustainable by facilitating women empowerment through village level gender sensitization programmes, need based training programmes and bringing genuinely interested farmers in farmers' club.